ATP13A2 deficiency induces a decrease in cathepsin D activity, fingerprint‐like inclusion body formation, and selective degeneration of dopaminergic neurons. Issue 9 (13th March 2013) - Matsui, Hideaki; Sato, Fumiaki; Sato, Shigeto; Koike, Masato; Taruno, Yosuke; Saiki, Shinji; Funayama, Manabu; Ito, Hidefumi; Taniguchi, Yoshihito; Uemura, Norihito; Toyoda, Atsushi; Sakaki, Yoshiyuki; et al.
Abstract : Here, we report that normal ATP13A2 localizes in the lysosome, whereas disease‐associated variants remain in the endoplasmic reticulum. Cathepsin D activity was decreased in ATP13A2‐knockdown cells that displayed lysosome‐like bodies characterized by fingerprint‐like structures. Furthermore, an atp13a2 mutation in medaka fish resulted in dopaminergic neuronal death, decreased cathepsin D activity, and fingerprint‐like structures in the brain. Based on these results, lysosome abnormality is very likely to be the primary cause of KRS/PARK9. Abstract : ATP13A2 is a lysosomal protein but some disease-associated variants remain in the endoplasmic reticulum. Loss of ATP13A2 function in cells results in cell death, cathepsin D reduction and fingerprint-like structures. Atp13a2 mutant medaka discloses dopaminergic cell death, cathepsin D reduction and fingerprint-like structures.